Determining the relationship between leadership practices and leadership needs in Saudi construction companies - Abdulkarim Albahali Nasser (Journal of Engineering Management and Competitiveness, 2017)
Effective leadership is demonstrated by influencing and guiding the activities of the team toward achieving its goals. This study attempts to determine the relationship between leadership practices and leadership needs in construction companies in the Kingdom of Saudi Arabia. A postal questionnaire survey was conducted to achieve the main aim of this research. Questionnaires were mailed to 155 construction companies in Jeddah city between September and October 2012. Of these, only 138 questionnaires were returned and analyzed. Significant associations were found among all variables. It was found that the two dimensions' personal competence (B=0.370, t=4.393, p<0.01) and professional competence (B=0.312, t=3.05, p<0.01) as leadership needs were significant towards leadership practices. This study suggests that the company leader, director, executive and non-executive should give direct reports autonomously and encourage others to face challenges, solve problems, and develop their own accountability which could significantly increase the effectiveness of company leaders in the construction industry of the Kingdom of Saudi Arabia.